QURANIC APPROACH ABOUT SEXUALITY EDUCATION - M. A. Khan; S. Khan (Journal of Animal and Plant Sciences, 2015)
Sex has a vital importance in the life of human beings; propagation of human life and society at large is mainly dependent upon its disciplined fulfillment. Thus all the divine religions made the marriage as an institution of legal relationship between man and woman through the family system. It is understood that society and civilization require for their existence a certain amount of regulation of sexual expression. However, it is also a fact that what is seen as being beneficial to society is not always considered by an individual as being beneficial to him. Humanity has been dwindling between the two extremes with reference to sexuality. Today, porn is advertised under the banner of sex education by including it in the syllabus of some educational systems. In all times and at all levels of human culture instructions in the matters of sex have been closely bound up with the social mores and the prevailing codes of ethics applied to sexual conduct. In the development of these codes, religion has of course been a dominant factor. The Quranic teachings related to human sexuality are of the most sober nature, which have further been explained in different Traditions of the Holy Prophet. This paper discusses the Quranic verses related to some aspects of human sexuality as the most idealistic method of educatinghuman beings about this significant subject. We believe that if those provisions were not revealed, then Muslims may have diverted from accomplishing the path of natural sexual desire to unnatural lust.
Keywords: Quran; Tafseer; Sex Education; Human Sexuality in Islam; Haya; Modesty; Nikah; Nudity; Conjugal relations between spouses; Seduction